Gente, natureza e colonização: fabricação e comércio de madeiras na capitania do Grão-Pará (1755-1808) - BATISTA, Regina Célia Corrêa (Universidade Federal do Pará, 2024)
The potential of the vast forest cover in the states of Grão-Pará and Maranhão, a region that covers most of the territory of the current Brazilian Amazon, generated early interest for the European colonizer. From the mid-18th century onwards, documentation from the period records intense wood production activity in the captaincy of Grão-Pará, produced in factories located near the rivers Moju, Acará, Igarapé-Miri, Abaetetuba, Barcarena, Vila do Conde, Maguari and Caraparú. In dialogue with historiography and based on handwritten and printed sources, this study seeks to analyze the intense manufacturing of wood in the captaincy and its intrinsic participation in the colonization process throughout the second half of the 18th and early 19th centuries. We argue that logging activity favored the colonization process in the captaincy of Grão-Pará, with its use being evident in supplying the Royal Arsenals of the Navy and Army in the Court, as well as being present in different aspects of the residents' lives, such as in the construction of houses, furniture and vessels, the main means of movement of people and goods in that period.